Effect Of Special Tool Completeness During Regular Service At Two Official Honda Workshops (HCM & CPM) Padang On Customer Satisfaction - Dian Wahyu (Jurnal Teknik Mesin, 2018)
AHASS HCM and CPM workshops are Honda's official workshops separated by a distance of only 1.6 km located in the city of Padang. The number of customers in these two workshops is very much different, even though the HCM workshop has a better form of building and facilities compared to the CPM workshop. Research needs to be done to see the factors that influence customer interest in choosing a workshop. Performing regular service requires equipment. Tools that are often overlooked are special tools. If the workshop does not have special tools, the mechanics will have difficulty in the process of dismantling and installing or adjusting, so that the impact on the performance of the motorcycle that has been serviced. Research on the effect of the completeness of special tools during regular service at two official Honda workshops (HCM & CPM) in Padang on customer satisfaction has been successfully carried out and the results show a significant difference. The measurement of the influence of special tools on customer satisfaction is measured using the SERVQUAL method, so that service quality in both workshops can be seen. The SERVQUAL method uses several dimensions (tangible, reliability, responsiveness, assurance, empathy) which will then be translated into 16 variables as indicators to create programs that can control services oriented to customer satisfaction. The results showed that both workshops (HCM and CPM) had a gap between perception and expectations in each dimension. The average total gap for each dimension is -0.44486 for the HCM workshop and -0.2902 for the CPM workshop. This shows that the quality of service expected by customers has not yet been achieved in both workshops, but the quality of service from CPM workshops is much better compared to HCM workshops. This causes more CPM workshop customers compared to HCM repair shops.